Comparative study of combined bevacizumab/targeted photocoagulation vs bevacizumab alone for macular oedema in ischaemic branch retinal vein occlusions. (19th May 2015) - Tomomatsu, Yoko; Tomomatsu, Takeshi; Takamura, Yoshihiro; Gozawa, Makoto; Arimura, Shogo; Takihara, Yuji; Inatani, Masaru
Abstract: Purpose: To investigate whether targeted retinal photocoagulation (TRP) of peripheral non‐perfused areas (NPAs) could prevent the recurrence of macular oedema (ME) due to branch retinal vein occlusion (BRVO) after intravitreal bevacizumab injection (IVB). Methods: Eyes received 1.25 mg IVB only (IVB group) or combined with TRP (IVB + TRP group) of NPAs, more than 5 disc areas identified by fluorescein angiography in the patients with ME secondary to BRVO. Best‐corrected visual acuity (BCVA) and central retinal thickness (CRT) determined by optical coherence tomography were measured every month for 6 months. Results: Thirty‐eight patients were enrolled and randomized to IVB group ( n  = 19) and IVB + TRP group ( n  = 19). Both groups showed similar thinning in CRT at 1 week after IVB, IVB + TRP group maintained thinner retina at 2 (p = 0.0072) and 3 (p = 0.0086) months compared with IVB group in whom turned to thickened almost back to baseline at 3 months. The number of reinjections in IVB group (1.58 ± 0.69) was significantly greater (p = 0.0025) than that in IVB + TRP group (0.83 ± 0.62). BCVA significantly improved at 6 month in IVB + TRP group (p = 0.015), but not in IVB group. Conclusion: TRP of NPAs reduced the amount of ME recurrence following IVB compared to IVB alone.